Synergistic effect between ischaemic heart disease and common mental disorders and the risk of premature exit from the labour market: a nationwide register based study from Sweden. (18th April 2017) - Mittendorfer-Rutz, Ellenor; Ivert, Torbjörn; Vaez, Marjan; Dorner, Thomas Ernst
Abstract: Aims: Common mental disorders i.e. depressive and anxiety disorders (CMD) are frequent comorbid conditions in individuals with ischaemic heart disease (IHD). Still, their effect on preterm exit from the labour market [i.e. disability pension (DP)] in individuals with IHD has to date not been scrutinized. The aim of this study was to investigate the separate and joint effect of IHD and CMD on the risk of DP for women and men of working age. Material and methods: This population-based cohort study included all non-pensioned 4 823 069 individuals, registered as living in Sweden 31 December 2004 and then 16–64 years of age. Individuals with IHD or CMD were identified through using data on sickness absence, prescribed medication or in- or specialized outpatient care in 2005. Crude and adjusted hazard ratios (HR) and 95% confidence intervals (CI) for being granted DP in 2006–10 were estimated by means of Cox proportional hazard regression. Results: In the fully adjusted models, HRs for DP were 2.84 (95% CI; 2.57–3.13) and 2.83 (2.66–3.01) in women and men with IHD, respectively. Hazard ratios for DP in women and men with CMD were 5.13 (5.03–5.24) and 6.08 (5.93–6.24). In women and men with both conditions, crude HRs for DP were 18.38 (15.01–22.50) and 25.58 (22.27–29.37). There was a significant synergistic effect between IHD and CMD in both sexes in the crude models, which disappeared in women after adjusting for socio-demographic variables, and in men after additionally adjusting for comorbid somatic disorders. Conclusion: A comorbid CMD worsens the prognosis of IHD in terms of early exit from the labour market. Processes leading to DP in individuals with IHD are multifactorial and may involve the presence of CMD as well as comorbidity with other somatic diseases.